2015
DOI: 10.1016/j.ebiom.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

3-D Imaging Reveals Participation of Donor Islet Schwann Cells and Pericytes in Islet Transplantation and Graft Neurovascular Regeneration

Abstract: The primary cells that participate in islet transplantation are the endocrine cells. However, in the islet microenvironment, the endocrine cells are closely associated with the neurovascular tissues consisting of the Schwann cells and pericytes, which form sheaths/barriers at the islet exterior and interior borders. The two cell types have shown their plasticity in islet injury, but their roles in transplantation remain unclear. In this research, we applied 3-dimensional neurovascular histology with cell traci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The Schwann cells should be mentioned in this context, since they seem to surround all islets in an envelope, but their functions remain enigmatic ( 7 ). It has been suggested that they may participate in regenerative processes after islet transplantation ( 8 ).…”
Section: Pancreatic Islet Morphologymentioning
confidence: 99%
“…The Schwann cells should be mentioned in this context, since they seem to surround all islets in an envelope, but their functions remain enigmatic ( 7 ). It has been suggested that they may participate in regenerative processes after islet transplantation ( 8 ).…”
Section: Pancreatic Islet Morphologymentioning
confidence: 99%
“…Third, in mouse development, the pancreatic/islet sympathetic innervation is important for islet formation and functional maturation [12]. Fourth, in mouse islet transplantation, the engrafted islets are able to remodel the surrounding sympathetic nerves and the associated glial cells to regain the islet innervation patterns [13,14], suggesting an intrinsic ability of islets to recruit and associate with neural tissues.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mouse glial cells form a sheath in the mantle of an islet to envelop the neuroendocrine tissue (39). In the pancreatic vasculature, blood vessels consist of endothelium and pericytes (or mural cells) (24,34). The endothelium recruits pericytes through the release of the plateletderived growth factor to establish physical contact from the abluminal direction to stabilize the vascular system (27,43).…”
Section: Transparent Mouse Pancreata With An Acinar Kras G12d Mutatiomentioning
confidence: 99%